Endoscopic Treatment of Early Gastric Obstruction After Sleeve Gastrectomy: Report of Two Cases - Costa, M (2016)
Morbid obesity is an epidemic and complex disease which imposes a multidisciplinary approach. Laparoscopic sleeve gastrectomy has become a frequent procedure given its efﬁ- cacy and safety compared to other surgical options. However, it isn’t free from complications. Lax gastric ﬁxation or incorrect positioning of the stomach during surgery can result in early gastric outlet obstruction caused by a volvulus-like mechanism by rotation of the stomach around its anatomic axes. This report refers to two cases of post sleeve gastric torsion resulting in persisting vomiting after initiating oral intake. The diagnosis was conﬁrmed by upper gastrointestinal-contrast study and gastroscopy. In both cases, a fully covered self-expandable metallic stentwas insertedwhich prompted the gastric lumen to become permeable resulting in symptomatic resolution. The stents were removed endoscopically aftertwo and three months. Beyond more than three years offollow-up,the patients remain asymptomatic and no recurring ‘‘stenosis’’ was noticed.In these cases the use offully covered self-expandable metallic stents demonstrated to be effective and safe in the treatment of post sleeve gastric torsion.